Clinicopathological profile of nasopharyngeal carcinoma in 2016-2019 at Dr. Soetomo General Hospital - Susetiyo, Karindra Amadea; Kusumastuti, Etty Hary; Yusuf, Muhtarum; Falerina, Rosa (Oto Rhino Laryngologica Indonesiana, 2022)
ABSTRACTBackground:.The number of nasopharyngeal carcinoma (NPC) cases is increasing and causing death, placing this cancer in fifth place as the cause of death in Indonesia. The initial clinical symptoms that are less specific often cause patients coming with advanced stage conditions. Therefore, the study of clinical and pathological profiles of NPC patients are required. Objective: To find out the clinicopathological profile of  NPC patients in Dr. Soetomo General Hospital in 2016-2019. Methods: This study was descriptive research with a retrospective study using medical records of NPC patients in Dr. Soetomo General Hospital from 2016 to 2019. Results:  192 NPC patients that meet the criteria were divided according to their age, gender, histopathological classification, stage, and post-therapy response. Out of 192 patients, 22 patients had post-therapy response based on histopathological data. Conclusion: NPC patients in Dr. Soetomo General Hospital in 2016-2019 were found in the range of 14-77 years old, most patients were in the age group 41-≤50 years old (66 patients, 34%). There were more male than female patients (73%). The most common clinical symptoms experienced by patients were a lump on the neck (82%), local ear complaints (79%), and local nasal complaints (75%). The most common histopathological subtype was non-keratinizing squamous cell carcinoma undifferentiated in 181 patients (94%). The highest stage of patients was IV A in 122 patients (64%). In 18 (82%) from 22 patients, based on histopathology examination had good criteria on therapy response. ABSTRAKLatar belakang: Angka kasus karsinoma nasofaring yang (KNF) kian meningkat dan dapat menyebabkan kematian, menempatkan kanker ini pada urutan ke lima di Indonesia. Gejala klinis awalnya yang kurang spesifik seringkali menyebabkan penderita datang dengan kondisi stadium lanjut. Oleh karena itu, profil penderita KNF secara klinis dan gambaran histopatologinya perlu diteliti lebih lanjut. Tujuan: Mengetahui profil klinikopatologi penderita KNF di RSUD Dr. Soetomo tahun 2016-2019. Metode: Penelitian secara deskriptif dengan studi retrospektif menggunakan rekam medis penderita KNF di RSUD Dr. Soetomo tahun 2016-2019. Hasil:  Sebanyak 192 penderita KNF yang memenuhi kriteria dibagi berdasarkan kategori usia, jenis kelamin, klasifikasi histopatologi, stadium, dan respon pasca terapi. Dari 192 penderita ditemukan sebanyak 22 penderita memiliki data respon pasca terapi berdasarkan histopatologi. Kesimpulan: Penderita KNF di RSUD Dr.Soetomo tahun 2016-2019 ditemukan pada rentang usia 14-77 tahun dengan penderita terbanyak pada rentang usia 41- 50 yaitu 66 (34%) serta lebih banyak terjadi jenis kelamin laki-laki yaitu 140 (73%). Gejala klinis yang paling banyak dialami penderita adalah benjolan pada leher 158 (82%), keluhan lokal telinga 151 (79%), dan lokal hidung 144 (75%). Subtipe histopatologi terbanyak adalah nonkeratinizing squamous cell carcinoma undifferentiated yaitu 181 (94%) penderita. Stadium terbanyak penderita adalah IV A yaitu 122 (64%) penderita. Sebanyak 18 (82%) dari 22 penderita berkriteria baik pada respon terapi berdasarkan histopatologi.